Unresolved issues and new challenges to the law of the sea : time before and time after - Stratē, Anastasia; Gavouneli, Maria; Skourtos, Nikolaos (Publications on ocean development ;, 2006)
Aimed at those interested in the law of the sea, this book analyzes topics, such as: the management of shared fish stocks, protection of the underwater cultural heritage, the possibilities of establishing marine protected areas and other means for safeguarding vulnerable marine ecosystems, and, the use of the high seas for intelligence.